Sdgs Number 11: Candirejo Village As Starting Point for Surabaya Sustainable City - Zahra, Nadia Devina Fathimatuz; Ramadhani, Tasya Rachmadila (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This study investigates the implementation of Sustainable Development Goal (SDG) 11, focusing on sustainable cities and communities, in Candirejo Village, Surabaya. We explore how Candirejo Village can serve as a model for urban sustainability in Surabaya, aligning with SDG 11 objectives. Using qualitative research methods based on direct observations in Candirejo Village, we identified key components supporting sustainability, employing the urban resilience approach from the Brundtland sustainability concept. Notable initiatives include the recycling of household wastewater for catfish cultivation, hydroponic systems, and herbal plant cultivation. These practices not only demonstrate environmental sustainability but also generate marketable products, contributing to household incomes in the village. By showcasing these local-level sustainability efforts, this research aims to provide insights into how grassroots initiatives can contribute to the broader goal of transforming Surabaya into a sustainable city and community, in line with SDG 11. The findings suggest that focusing on village-level sustainability practices could be an effective strategy for achieving city-wide sustainable development in Surabaya. The study underscores the importance of village-level environmental security and sustainability practices as effective strategies for achieving broader urban sustainability goals, even in densely populated city centers